Welcome to the New Bond Law Review - Iain Field (Bond Law Review)
The nature of the contemporary research environment and an increase in competition impel conventional lawjournals to address a number of uncomfortable questions concerning their future relevance and viability: Dolaw journals continue to serve the needs the profession and the academy (assuming that they ever did)? Forhow long will subscribers continue to pay individual journals for access to content, or to purchase hardcopy?Are law journals antiquated relics of a by-gone era, ill-suited to the realities of modern legal scholarship andthe demands of an increasingly complex market, or are they among the last bastions of quality in a woldsaturated in blogs, tweets and wikis? The reforms that we at BLR have implemented, and the characteristicsthat we seek to inculcate, reflect our considered response to questions such as these.